Epidemiology and distribution of interstitial lung diseases in Turkey. (31st July 2013) - Musellim, Benan; Okumus, Gulfer; Uzaslan, Esra; Akgün, Metin; Cetinkaya, Erdogan; Turan, Onur; Akkoclu, Atila; Hazar, Armagan; Kokturk, Nurdan; Calisir, Haluk Celalettin
Abstract Introduction There is very few data on the epidemiological features of interstitial lung diseases (ILD) in the literature. These studies on this subject suffer from limited number of patients. Objective The goal of this study was to evaluate the epidemiological features of ILD in Turkey. Methods Fifty‐four investigators, 31 centres in 19 cities from six regions of Turkey, participated in the study. Two thousand two hundred forty‐five newly diagnosed patients (51.8% females), led by Turkish Thoracic Society Clinical Problems Study Group, enrolled in this prospective study. Results The mean age was 51.8 ± 16.7 years. The mean age among males was 50.5 ± 18.6 years and 53.0 ± 14.6 years among females (P < 0.001). 23.8% of the cases had ILD with known causes, while 39.4% were in granulomatous group, 23.7% were idiopathic, and 4.4% were in the unclassified group. Overall, histopathologically confirmed diagnosis rate was 40.4%. Sarcoidosis was the most common disease (37%), whereas cases with idiopathic pulmonary fibrosis (IPF) constituted 19, 9% of patients. 53% of the sarcoidosis patients were females, and the ratio reaches to 75% under 50 years of age (for this group, IPF ratio is %3). In contrast, sarcoidosis and IPF ratios were equal in males (25%). Sarcoidosis was 8% in men over 50, while IPF was %45. Conclusion The overall incidence of ILD in Turkey was computed to be 25.8/100 000.